2020
DOI: 10.1186/s42787-020-00079-3
|View full text |Cite
|
Sign up to set email alerts
|

Roles of nanoparticles and heat generation/absorption on MHD flow of Ag–H2O nanofluid via porous stretching/shrinking convergent/divergent channel

Abstract: This article unveils the combined impact of heat generation/absorption and Joule heating on MHD flow of Ag-H 2 O nanofluid into a porous stretching/shrinking divergent/ convergent channel with viscous dissipation and solid volume fraction. The mathematical modeling is presented for the existing equations of continuity, momentum, and energy fraction. The reduced boundary value problem is solved numerically employing Runge-Kutta-Fehlberg (RKF) method via shooting scheme and then the outcomes are sketched and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…The dimensionless set of flow Equations (19) to (21) along with assisted boundary conditions (22) is solved numerically implementing shooting scheme using RKF45 order technique. The description of RKF45 technique is based on a study by Mishra et al, 27 Mishra and Kumar, 39 and Makinde et al 43 The numerical process is confirmed by doing a comparison with previous findings for θ − ′(0) with different values of Pr. The comparison exhibits an excellent match (see Table 2).…”
Section: Numerical Solutionmentioning
confidence: 78%
See 2 more Smart Citations
“…The dimensionless set of flow Equations (19) to (21) along with assisted boundary conditions (22) is solved numerically implementing shooting scheme using RKF45 order technique. The description of RKF45 technique is based on a study by Mishra et al, 27 Mishra and Kumar, 39 and Makinde et al 43 The numerical process is confirmed by doing a comparison with previous findings for θ − ′(0) with different values of Pr. The comparison exhibits an excellent match (see Table 2).…”
Section: Numerical Solutionmentioning
confidence: 78%
“…The effective thermophysical properties of Ag–water nanofluid are described as follows 27,33 : Density: ρnf=false(1φfalse)ρbf+φρsp. Specific heat capacity: false(ρCpfalse)nf=false(1φfalse)false(ρCpfalse)bf+φfalse(ρCpfalse)sp. Dynamic viscosity: μnf=false(1φfalse)2.5μbf. Thermal conductivity: κnfκbf=false(κsp+2κbffalse)2φfalse(κbfκspfalse)false(κsp+2κbffalse)+φfalse(κbfκspfalse).…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Boundary conditions of the model are Now, q ′′′ is defined as where Q and Q 0 are internal heat source parameters. The theoretical model for nanofluid transport is defined as follows [11,18,[32][33][34]:…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The skin-friction coefficient at the wall of the channel is represented by the mathematical expression C f as 33 :…”
Section: Mathematical Formulation and Flow Configurationmentioning
confidence: 99%